Differentiation of Sex Chromosomes and Karyotype Characterisation in the Dragonsnake Xenodermus javanicus (Squamata: Xenodermatidae) - Rovatsos, Michail; Johnson Pokorná, Martina; Kratochvíl, Lukáš (Cytogenetic and genome research, 2015)
Highly differentiated heteromorphic ZZ/ZW sex chromosomes with a heterochromatic W are a basic principle among advanced snakes of the lineage Colubroidea, while other snake lineages generally lack these characteristics. For the first time, we cytogenetically examined the dragonsnake, Xenodermus javanicus, a member of the family Xenodermatidae, which is phylogenetically nested between snake lineages with and without differentiated sex chromosomes. Although most snakes have a karyotype with a stable chromosomal number of 2n = 36, the dragonsnake has an unusual, derived karyotype with 2n = 32 chromosomes. We found that heteromorphic ZZ/ZW sex chromosomes with a heterochromatic W are present in the dragonsnake, which suggests that the emergence of a highly differentiated W sex chromosome within snakes predates the split of Xenodermatidae and the clade including families Pareatidae, Viperidae, Homalopsidae, Lamprophiidae, Elapidae, and Colubridae. Although accumulations of interstitial telomeric sequences have not been previously reported in snakes, by using FISH with a telomeric probe we discovered them in 6 pairs of autosomes as well as in the W sex chromosome of the dragonsnake. Similarly to advanced snakes, the sex chromosomes of the dragonsnake have a significant accumulation of repeats containing a (GATA)n sequence. The results facilitate the dating of the differentiation of sex chromosomes within snakes back to the split between Xenodermatidae and other advanced snakes, i.e. around 40-75 mya.
Keywords: hadi; Sex Chromosomes; polymerázová řetězová reakce; Male; pohlavní chromozomy; karyotypizace; hybridizace in situ fluorescenční; fylogeneze; mikrosatelitní repetice; Sex Determination Processes; Phylogeny; Karyotyping; karyotyp; biologická evoluce; mužské pohlaví; Microsatellite Repeats; Animals; ženské pohlaví; Biological Evolution; zvířata; In Situ Hybridization, Fluorescence; Snakes; Polymerase Chain Reaction; procesy určující pohlaví; Female; Karyotype